Factors associated with delayed diagnosis of pulmonary tuberculosis with positive bacilloscopy in Bangui, Central Africa - Longo, Jean de Dieu; Diemer, Henri Saint Calvaire; Woromogo, Sylvain Honoré; Doyama-woza, Herman; Gotia-Dondoumba, Gaby Ferreol Melkisedeck; Grésenguet, Gérard (International Journal Of Community Medicine And Public Health, 2023)
Background: A case of untreated bacteriologically confirmed pulmonary tuberculosis (BPT+) represents a reservoir for transmission of the disease. The objective of this study was to evaluate the delay and identify the determinants of the delay in the diagnosis of BPT+ in the diagnostic and treatment centers for tuberculosis (CDT) in Bangui. Methods: An analytical cross-sectional survey was conducted. It included all new TB patients aged 15 years and older (145) who presented a positive bascilloscopy. Exhaustive recruitment was performed during the study period. Multiple logistic regression with OR (95% CI) for p<0.05 was used to establish the relationship between delayed diagnosis and patient characteristics. Results: Patients ranged in age from 16 to 80 years with an average age of 33.81±12.18 years. The time to consultation and diagnosis >30 days after the onset of symptoms were 83.10% and 23.95%, respectively. In multivariate analysis, male patients [ORa=0.42 (0.19-0.93)]; patients residing in peri-urban areas [ORa=4.25 (2.10-9.02)]; patients using informal care facilities as first option [ORa=1.84 (1.47-3.38)] and not requesting acid-fast bacilli (AFB) test at first visit [ORa=6.09 (3.70-17.69)] were associated with risk of delayed diagnosis. Conclusions: Early diagnosis and treatment of BPT+, which is the spreading form of the disease, remains a public health concern in our context. Supervision and coaching of health workers coupled with increased public awareness of TB will contribute to better control of the disease.